Cell Membrane-Coated Biomimetic Nanoparticles in Cancer Treatment - Shu Zhang; Xiaojuan Zhang; Huan Gao; Xiaoqin Zhang; Lidan Sun; Yueyan Huang; Jie Zhang; Baoyue Ding (MDPI AG, 2024)
Nanoparticle-based drug delivery systems hold promise for cancer treatment by enhancing the solubility and stability of anti-tumor drugs. Nonetheless, the challenges of inadequate targeting and limited biocompatibility persist. In recent years, cell membrane nano-biomimetic drug delivery systems have emerged as a focal point of research and development, due to their exceptional traits, including precise targeting, low toxicity, and good biocompatibility. This review outlines the categorization and advantages of cell membrane bionic nano-delivery systems, provides an introduction to preparation methods, and assesses their applications in cancer treatment, including chemotherapy, gene therapy, immunotherapy, photodynamic therapy, photothermal therapy, and combination therapy. Notably, the review delves into the challenges in the application of various cell membrane bionic nano-delivery systems and identifies opportunities for future advancement. Embracing cell membrane-coated biomimetic nanoparticles presents a novel and unparalleled avenue for personalized tumor therapy.